Paul Celan in English: A Bibliography of Primary and Secondary Literature - Jerry Glenn (Studies in 20th & 21st Century Literature, 1983)
A Bibliography of Primary and Secondary Literature of Paul Celan
Keywords: Paul Celan; poetry; poem; poetics; translation; English; German